Investigating the relationship between phonological awareness and reading using Event-Related Potentials - Fella, Argyro; Christoforou, Christoforos; Loizou-Papadopoulou, Maria; Papadopoulos, Timothy C. (Psychology: the Journal of the Hellenic Psychological Society, 2022)
The present study investigated the differences between children with reading difficulties (RD) and their controls (CA) (age range = 7.7–12.08 years; Mage = 9.79 years; SD=1.57; Females = 24) on two phonological awareness tasks (phoneme elision and spoonerism), using Event-Related Potentials. EEG data recording elicited the N400 component in both tasks. The results revealed that 8-year-old children with RD produced significantly longer Ν400 than their CA controls in phoneme elision task, suggesting that younger children with RD require more time to process the phonological stimuli than their peers. No differences were observed in N400 components between the 11-year-olds, showing that the RD children outgrow difficulties in phonological awareness tasks due to the consistency of the Greek writing system. The RD and CA groups did not differ in the spoonerism task, probably due to the task’s increased complexity. Discussion centers around the role of Event-Related Potentials in providing valuable information about the phonological mechanisms underpinning reading.